Biased Perceptions of Racially Diverse Teams and Their Consequences for Resource Support - Lount, Robert B.; Sheldon, Oliver J.; Rink, Floor; Phillips, Katherine W. (Organization Science, 2015)
We examine whether observers hold biases that can negatively affect how racially diverse teams are evaluated, and ultimately treated, relative to racially homogeneous groups. In three experiments, which held the actual content of observed behavior constant across diverse and homogeneous teams, observers were less willing to allocate additional resources to diverse teams. Through applying both statistical mediation (Studies 1 and 2) and moderation-of-process methods (Study 3), our findings supported the expectation that biased perceptions of relationship conflict accounted for this reduced support of diverse teams. Implications for diverse teams in organizations are discussed.